Medical Molecular Morphology - Senda, Takao; SpringerLink (Online service) (Singapore : Springer Singapore : Imprint: Springer.)
Medical Molecular Morphology is an international forum for researchers in both basic and clinical medicine to present and discuss new research on the structural mechanisms and the processes of health and disease at the molecular level. The structures of molecules, organelles, cells, tissues, and organs determine their normal function. Disease is thus best understood in terms of structural changes in these different levels of biological organization, especially in molecules and molecular interactions as well as the cellular localization of chemical components. Medical Molecular Morphology welcomes articles on basic or clinical research in the fields of cell biology, molecular biology, and medical, veterinary, and dental sciences using techniques for structural research such as electron microscopy, confocal laser scanning microscopy, enzyme histochemistry, immunohistochemistry, radioautography, X-ray microanalysis, and in situ hybridization. Manuscripts submitted for publication must contain a statement to the effect that all human studies have been reviewed by the appropriate ethics committee and have therefore been performed in accordance with the ethical standards laid down in an appropriate version of the 1964 Declaration of Helsinki. It should also be stated clearly in the text that all persons gave their informed consent prior to their inclusion in the study. Details that might disclose the identity of the subjects under study should be omitted. Reports of animal experiments must state that the "Principles of laboratory animal care"(NIH publication No. 86-23, revised 1985) were followed. The Editor-in-Chief reserves the right to reject manuscripts that do not comply with the above-mentioned requirements. The author will be held responsible for false statements or for failure to fulfil the above-mentioned requirements. .
Keywords: Molecular biology; Human anatomy; Pathology; Pathology; Anatomy; Molecular Medicine